(8x+6y-4)+(7x+12y-5)=

Simple and best practice solution for (8x+6y-4)+(7x+12y-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+6y-4)+(7x+12y-5)= equation:


Simplifying
(8x + 6y + -4) + (7x + 12y + -5) = 0

Reorder the terms:
(-4 + 8x + 6y) + (7x + 12y + -5) = 0

Remove parenthesis around (-4 + 8x + 6y)
-4 + 8x + 6y + (7x + 12y + -5) = 0

Reorder the terms:
-4 + 8x + 6y + (-5 + 7x + 12y) = 0

Remove parenthesis around (-5 + 7x + 12y)
-4 + 8x + 6y + -5 + 7x + 12y = 0

Reorder the terms:
-4 + -5 + 8x + 7x + 6y + 12y = 0

Combine like terms: -4 + -5 = -9
-9 + 8x + 7x + 6y + 12y = 0

Combine like terms: 8x + 7x = 15x
-9 + 15x + 6y + 12y = 0

Combine like terms: 6y + 12y = 18y
-9 + 15x + 18y = 0

Solving
-9 + 15x + 18y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 15x + 9 + 18y = 0 + 9

Reorder the terms:
-9 + 9 + 15x + 18y = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 15x + 18y = 0 + 9
15x + 18y = 0 + 9

Combine like terms: 0 + 9 = 9
15x + 18y = 9

Add '-18y' to each side of the equation.
15x + 18y + -18y = 9 + -18y

Combine like terms: 18y + -18y = 0
15x + 0 = 9 + -18y
15x = 9 + -18y

Divide each side by '15'.
x = 0.6 + -1.2y

Simplifying
x = 0.6 + -1.2y

See similar equations:

| f(x)=x^2-2x+6 | | 1024+x^2=256+x^2 | | 5ln(4x+9)=35 | | 8x-9y-5z=16 | | 4sec^2x+2tan^2x-6=0 | | 7ln(3x+10)=42 | | 4x-5x=8x-9+11x | | 2*(7/2X) | | 3(3-x)=5(2x-7)+2 | | (-2/9)=4/a | | -9-6+3= | | 9(11-k)=9(x-5) | | r(6r+1)=12 | | 1/4x-1/6x=100 | | 59=-75 | | (5a-2b)+(3a-4b)=0 | | 8(w+3)+4=-7w+11 | | 90x+50=100x | | 4(5-x)=-4.9+2.1(6x) | | 5(x+1)-2(x-1)=12 | | -(v+9)+7=-7v-12 | | -15x+8=7-15x | | 9p+7=6+3(p-1) | | x=x^2+6x+15 | | 9q+7=6+3(p-1) | | 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) |

Equations solver categories